Lower circulating angiotensin II levels are related to the severity of preeclampsia and its risk as disclosed by a specific bioassay. Issue 39 (September 2018) - Leaños-Miranda, Alfredo; Inova Campos-Galicia,; Méndez-Aguilar, Francisco; Molina-Pérez, Carlos José; Ramírez-Valenzuela, Karla Leticia; Sillas-Pardo, Liliana Janet; Uraga-Camacho, Navid Claudian; Isordia-Salas, Irma; Berumen-Lechuga, María Guadalupe
Abstract : Abstract: Preeclampsia is characterized by an increased sensitivity to angiotensin II (Ang II). We herein assessed whether serum Ang II levels measured by a new developed bioassay are associated with preeclampsia, its severity, and the risk for developing this disease. Using a cross-sectional design, we studied 90 pregnant women (30 healthy pregnant and 60 with preeclampsia [30 with- and 30 without severe features]). We also used a nested case-control study with 30 women who eventually developed preeclampsia and 31 normotensive controls. Serum samples were collected at diagnosis of preeclampsia or at 4-week intervals (from weeks 12th to 36th). Ang II was measured using a bioassay. At diagnosis of preeclampsia, serum Ang II concentrations were significantly lower in preeclampsia without and with severe features ( P  = .001 and P  < .001, respectively) than in healthy pregnancy. In addition, Ang II was different in preeclampsia with severe features than in those without severe features ( P  = .048). Women who subsequently developed preeclampsia had lower Ang II levels than women with normal pregnancies, and these changes became significant at 24 weeks onward. The risk to developing preeclampsia was higher among women with Ang II concentration values in the lowest quartile of the control distribution from 12 weeks onward (odds ratio ranging from 3.8 [95% CI 1.3–11.1] to 6.5 [95% CI 1.6–26.9]). We concluded that concentrations of Ang II are markedly diminished at diagnosis of preeclampsia and are closely associated with the severity of disease. Changes in circulating levels of Ang II precede the clinical presentation of preeclampsia.